Bacteria detected in the honeybee parasitic mite Varroa destructor collected from beehive winter debris - Hubert, J; Erban, T; Kamler, M; Kopecky, J; Nesvorna, M; Hejdankova, S; Titera, D; Tyl, J; Zurek, L (Journal of applied microbiology, 2015)
AIMS: The winter beehive debris containing bodies of honeybee parasitic mite Varroa destructor is used for veterinary diagnostics. The Varroa sucking honeybee haemolymph serves as a reservoir of pathogens including bacteria. Worker bees can pick up pathogens from the debris during cleaning activities and spread the infection to healthy bees within the colony. The aim of this study was to detect entomopathogenic bacteria in the Varroa collected from the winter beehive debris. METHODS AND RESULTS: Culture-independent approach was used to analyse the mite-associated bacterial community. Total DNA was extracted from the samples of 10 Varroa female individuals sampled from 27 different sites in Czechia. The 16S rRNA gene was amplified using universal bacterial primers, cloned and sequenced, resulting in a set of 596 sequences representing 29 operational taxonomic units (OTU97). To confirm the presence of bacteria in Varroa, histological sections of the mites were observed. Undetermined bacteria were observed in the mite gut and fat tissue. CONCLUSION: Morganella sp. was the most frequently detected taxon, followed by Enterococcus sp., Pseudomonas sp., Rahnella sp., Erwinia sp., and Arsenophonus sp. The honeybee putative pathogen Spiroplasma sp. was detected at one site and Bartonella-like bacteria were found at four sites. PCR-based analysis using genus-specific primers enabled detection of the following taxa: Enterococcus, Bartonella-like bacteria, Arsenophonus and Spiroplasma. SIGNIFICANCE AND IMPACT OF THE STUDY: We found potentially pathogenic (Spiroplasma) and parasitic bacteria (Arsenophonus) in mites from winter beehive debris. The mites can be reservoirs of the pathogenic bacteria in the apicultures.
Keywords: Animals; winter wax debris; Spiroplasma; Female; Seasons; ženské pohlaví; pathogen; Apis mellifera; RNA, Ribosomal, 16S; Varroidae; Molecular Sequence Data; bacteria feeding; roční období; Phylogeny; Arsenophonus; molekulární sekvence - údaje; Male; diagnostics; Bacteria; Bees; pathogen detection; včely; mužské pohlaví; zvířata; fylogeneze; RNA ribozomální 16S; Varroa destructor